Pharmaceutical Care dan Kepatuhan Minum Obat Hipertensi Terhadap Lansia Dengan Hipertensi - Ayu Wandira; Cindiansya Cindiansya; Jihan Rosmayati; Riswanti Frida Anandari; Sri Anbar Naurah; Maya Arfania; Dedy Frianto (Peneliti.net, 2023)
Elderly people (elderly) refer to people aged 60 years or more. Elderly people (elderly) are at high risk for various degenerative diseases that usually show no symptoms when they are young, namely hypertension. Hypertension is called the